PENGARUH ARUS KAS OPERASI, LABA BERSIH, DAN HUTANG TERHADAP KEBIJAKAN DIVIDEN (DIVIDEND PAYOUT RATIO) PADA PERUSAHAAN MANUFAKTUR YANG GO PUBLIC DI BURSA EFEK INDONESIA TAHUN 2005-2009 - Neny Tikana, ; Susi Handayani, (Bisnis dan Manajemen, 2011)
In the expansion, companies need a lot of sources of funding, that is through capital markets. Capital markets are an alternative source of external funding sources in addition to loan funds. With the capital markets, investor can invest in many different investment options, one of which is stock. Return the stock received by investors may include capital gains and dividends. Dividend is a part of the projected dividendd policy with a dividend payout ratio (DPR). Dividend policy is influenced by several factors including the operating cash flow, net income, and debt. The purpose of this study was to examine and analyze the influence of operating cash flow, nt income, and debt to dividend policy (dividend payout ratio) at a manufacturing company that went public on the Indonesia Stock Exchange in 2005-2009. This study uses purposive sampling method to take samples, in order to obtain a sample number 27 manufacturing companies. The method of analysis used is multiple linear regression analysis with the help of analysis tools SPSS version 16.0 Based on the results of data analysis can be concluded that there is a simultaneous influence of operating cash flow, net income, and debt to dividend policy (dividend payout ratio). While partial, operating cash flow negative influence on dividend payout ratio. That is because the large cash is not necessarily distibuted as dividends, because dividends depend essentially on the policy of the company itself and the profits of the acquired companies. Net income has a positive effect on dividend payout ratio for dividends derived from net income and companies will share profits if it makes a profit. The Debt has negative effect on dividend payout ratio for firms to prioritize paying off debt rather than dividends